30/x - 30/(x-1) = -1
Multiply everything by x(x-1)
(30/x)x(x-1) - (30/(x-1))x(x-1) = -1x(x-1)
30(x-1) - 30(x) = -x^2 + x
30x - 30 - 30x = -x^2 + x
Move everything to the left side and cancel 30x
x^2 -x - 30 = 0
(x-6)(x+5) = 0
x - 6 = 0 or x + 5 = 0
x = 6 or x = -5
2006-12-12 07:58:02
·
answer #1
·
answered by MsMath 7
·
1⤊
1⤋
I'm assuming you mean 30/x - 30/(x-1) = -1, or otherwise your equation would be 0 = 0. So, we'll assume the first.
First step is to multiply the whole equation (both sides) by x-1.
[30(x-1)]/x - 30 = -(x-1)
Second step is to multiply the entire equation by x.
30(x-1) - 30x = -x(x-1)
x^2 - x - 30 = 0
(x-6)(x+5)=0
x = 6,-5
2006-12-12 08:01:51
·
answer #2
·
answered by slider 2
·
1⤊
0⤋
I assume you mean
30/x - 30/(x-1) = -1
(A reminder that brackets are important because they show that they are ALL on the bottom. If the above is not what you meant, I apologize in advance.)
In order to get rid of all fractions, you multiply both sides by
(x)(x-1). This will get rid of the fractions on the left hand side, leaving a product to be multiplied behind.
30(x-1) - 30(x) = -1(x)(x - 1)
Now, expand, to get
30x - 30 - 30x = (-1)(x^2 - x)
And expand some more
-30 = -x^2 + x
And then bring everything over to the left hand side
x^2 - x - 30 = 0
Factoring, we get
(x - 6)(x+5) = 0
Therefore, x = 6, -5
2006-12-12 07:59:49
·
answer #3
·
answered by Puggy 7
·
1⤊
0⤋
if you mean
(30/x) - (30/x) - 1 = -1
then the answer is:
(30/x) - (30/x) - 1 = -1
(30/x) - (30/x) = 0
30/x = 30/x
1/x = 1/x
x = x
x = all numbers
However if you mean:
(30/x) - 30/(x-1) = -1
then the answer is:
(30/x) - 30/(x-1) = -1
30*(x-1) - 30*x = -1*x*(x-1)
30x -30 -30x = -x*x + x
x^2 -x -30 = 0
(x-6)*(x+5) = 0
x = 6, -5
2006-12-12 08:02:53
·
answer #4
·
answered by Andy M 3
·
1⤊
0⤋
the LCD is x(x-1)
30(x-1)-30x=-1x(x-1)
30x-30-30x=-x^2+x
-30=-x^2+x
adding x^2-x
x^2-x-30=0
(x-6)(x+5)=0
x=6 or -5
2006-12-12 07:55:21
·
answer #5
·
answered by raj 7
·
2⤊
0⤋
x= 6
x= -5
2006-12-12 07:58:05
·
answer #6
·
answered by Anonymous
·
1⤊
1⤋